Алгоритм формирования и отбора тестов для регрессионного тестирования баз данных - Малинина, О.Ю. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2011)
Automation of regression testing is facing several problems such as the
difficulty of tests determining and the lack of cheap and effective tools for automation.
But it is necessary to create new approaches to regression testing and invent new tools
that could accelerate it. Article is devoted to the development of algorithm that is
aimed to simplify this process for systems which contain database (DB) stored
procedures.